Rhizobacterial compositions and their relationships with soil properties and medicinal bioactive ingredients in Cinnamomum migao - Li, Lixia; Yang, Xuedong; Tong, Bingli; Wang, Deng; Tian, Xiu; Liu, Jiming; Chen, Jingzhong; Xiao, Xuefeng; Wang, Shu (Frontiers in Microbiology, 2023)
Rhizobacterial communities and their metabolites can affect plant growth, development, and stress resistance, as well as the biosynthesis and accumulation of bioactive compounds in medicinal plants. This relationship has been well-characterized in many medicinal herbs, although much less commonly in medicinal trees. Here, we analyzed the composition and structure of Cinnamomum migao rhizobacterial communities across nine growing regions in Yunnan, Guizhou and Guangxi, China, as well as differences in soil properties and fruit bioactive compounds. Results showed that the C. migao rhizobacterial communities exhibited high species richness, but location-specific differences in structure. Site-specific differences in soil properties and bioactive compounds were also observed. Furthermore, rhizobacterial community compositions were correlated with both soil properties and fruit bioactive compounds. Functional analysis indicated that metabolism-related functions were most common in C. migao rhizobacteria. Several bacterial genera, including Acidothermus, Acidibacter, Bryobacter, Candidatus_Solibacter, and Acidimicrobiales, potentially promote the biosynthesis and accumulation of 1,8-cineole, cypressene, limonene, and α-terpineol, Nitrospira and Alphaproteobacteria may play an inhibitory role. Finally, our results emphasized the critical role that soil pH and nitrogen levels play in driving rhizobacterial community structure, and specific functional bacteria can also counteract with soil properties, Acidibacter and Nitrospira can affect soil pH and nitrogen effectiveness. Overall, this study provides additional insight into the complex correlation of rhizosphere microorganisms with bioactive ingredients and soil properties of medicinal plants.